The Status of Industrial Relations as an Academic Discipline Within Canadian Universities - Boivin, Jean (Relations industrielles / Industrial Relations, 1992)
This paper presents empirical evidence on the limited status of industrial relations as an academic discipline within Canadian universities. A survey conducted among the four "independent" Industrial Relations units and thirty two Business Administration faculties used the three following indicators: the number and content of academic programs dealing with industrial relations; the institutional status of academic units responsible for the administration of these programs; and the academic status of the persons involved in the delivery of industrial relations courses.